Intensive care and rehabilitation for an elderly patient with acute exacerbation of chronic renal failure (1例老年慢性肾衰竭急性加重患者的ICU康复护理) - KONG Tongtong (孔彤彤); SU Junqing (苏俊青); LIU Shuhua (刘书华) (中西医结合护理)
This paper reviewed the intensive care and rehabilitation management for an elderly patient with acute exacerbation of chronic renal failure, and exercise program on respiratory function, lower-limb function and prevention of thrombosis development were summarized and analyzed. (本文回顾1例高龄慢性肾衰竭急性加重患者的ICU康复护理措施, 从呼吸功能的锻炼恢复、下肢功能锻炼预防血栓形成等方面总结护理经验。)